The Byzantine system from within: a comparison of Procopius' Secret History and Lydus' On the Magistracies, and their presentation of the regime of Justinian - Carew, Gregory (Classical Studies, 2024)
[pg 124,129 is missing] The reason for choosing Procopius and John the Lydian (or Lydus, as he will be referred to for convenience hereafter) for this study of the reign of Justinian is that they both provide contemporary accounts from within the imperial system and portray different persepectives on the reactions to radical change. In this regard, it will be argued that Procopius reflected a reactionary aristocratic point of view and Lydus a bureaucratic one, yet their origins were similar. In his useful content analysis on the work of Lydus, Carney describes him as a representative of the sub-elite. Although the work of other sources contemporary to the reign of Justinian, or dealing with it directly in the later Byzantine period, will be referred to, the comparison in this discussion has been made between Lydus and Procopius for a number of reasons. Firstly, Procopius is by far the most detailed and comprehensive source for the reign of Justinian extant. Moreover, although he doesn't emphasize the role of Christianity in this period in the same manner that those writing ecclesiastical histories and world chronicles do, he has left us with three very different works from different perspectives on Justinian's reign, yet bearing a commonality. Lydus in turn, although not producing a classic of literature as such, has left us with three works detailing aspects of the Roman use of the calendar, portents and the functioning and history of the civil service. The two works that I shall be considering in the most detail will be Procopius' Secret History (or Anecdota, hereafter S.H.) and Lydus' On the Magistracies (referred to for convenience by its Latin title De Magistratibus, abbreviated to De Mag.). At first glance, the former appears unique in classical literature, yet it will be argued that it was not entirely without precedent and needs to be seen in its literary and historical context. Furthermore, the emphasis that it places on administrative history makes it a suitable comparison to Lydus. The latter, however was less controversial, but reveals unique details about one writer's attempt to understand what Justinian's changes meant and what their effect on the Praetorian Prefecture was (which by the reign of Justinian had become the most powerful magistracy in the empire).